Rapid repair of RC columns with post-tensioned external clamps - Rincón, Julián D; Pujol, Santiago (Bulletin of the New Zealand Society for Earthquake Engineering, 2024)
A recent technique for repair of damaged reinforced concrete (RC) columns is reviewed. The technique involves the application of external post-tensioned clamps. The clamps are composed of steel angles and high-strength steel rods. The pairs of angles are placed on the corners of the cross-section, and they are connected with steel rods to each other. To evaluate the effectiveness of the repair technique, four large-scale RC columns with insufficient transverse reinforcement were subjected to lateral displacement reversals and constant axial load. The tests were conducted in two phases: initial testing of columns with none to light transverse reinforcement, followed by the application of clamps on the damaged columns and further testing. The study focused on the efficacy of the clamps to a) restore the lateral-carrying capacity of damaged RC columns, and b) increase drift capacity. Variations in lateral expansion of the column core and their plausible correlations with damage and ‘repairability’ are examined. Within the conditions investigated, two key requirements are proposed for safe column repair: 1) the concrete in damaged columns with cross-sectional expansion exceeding 1% should be replaced or repaired before clamps are applied as a repair measure, and 2) clamps should be proportioned to resist 100% of the maximum plausible shear demand even though perceptible contributions to shear resistance attributable to the concrete were observed in columns repaired before excessive expansion occurred. In columns with crisscrossing inclined cracks leading to lateral cross-sectional expansion of up to 1%, clamps were observed to provide effective shear resistance comparable to what conventional transverse reinforcement can provide.